2020
DOI: 10.2514/1.j058756
|View full text |Cite
|
Sign up to set email alerts
|

Liner Impedance Eduction Under Shear Grazing Flow at a High Sound Pressure Level

Abstract: This paper investigates the combined effects of high sound pressure level and grazing flow on impedance eduction for classical liners. Experiments are conducted in the grazing flow duct at ONERA (B2A). The impedance is then educed with an inverse method adapted to a shear flow. To take into account the effects of incident sound pressure level, a new strategy for impedance eduction is developed, using a space-dependent variable term. The new strategy is applied to different experimental cases and the results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 31 publications
(26 reference statements)
4
21
1
Order By: Relevance
“…Beck et al [25] and Billard et al [26] used a similar iterative strategy to match the impedance measurements obtained in a normal incidence tube configuration. Lafont et al [27] showed that not accounting for the decrease in SPL above the liner during the eduction process could cause a bias in the educed resistance value. A straightforward heuristic was used in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beck et al [25] and Billard et al [26] used a similar iterative strategy to match the impedance measurements obtained in a normal incidence tube configuration. Lafont et al [27] showed that not accounting for the decrease in SPL above the liner during the eduction process could cause a bias in the educed resistance value. A straightforward heuristic was used in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A straightforward heuristic was used in Ref. [27] to model the spatial variation of the impedance, i.e., a monotonously decreasing function of the real part of the resistance was taken, with a threshold value indicating the position above the liner at which no nonlinear effect would be triggered anymore. A decrease in the acoustic resistance can indeed be expected as the amplitude of the wave decreases on top of the liner, given the known nonlinear acoustic behavior of liners at normal incidence [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a clear gap between the behavior at low flow speeds ( smaller than 0.1) and at higher flow speeds; this gap confirms that the coupling between thermal and acoustic effects is competing with the grazing flow effect. This competition between the influences of high SPL and high flow speeds has been previously studied [24]: it was found that for Mach numbers lower than 0.1, the acoustic effects dominate, but are gradually overwhelmed by the grazing flow until they become too small to be captured.…”
Section: B Influence Of the Direction Of The Thermal Gradientmentioning
confidence: 80%
“…9 and using a minimization method where experimental and numerical results are compared. The numerical resolution of the LEE is done with a discontinuous Galerkin (DG) scheme, accounting naturally for the presence of a shear grazing flow in the simulation [19,23,24].…”
Section: B Impedance Eductionmentioning
confidence: 99%